Inflation risk premia in the US and the euro area - Peter Hördahl; Oreste Tristani (European Central Bank (ECB), 2010)
We use a joint model of macroeconomic and term structure dynamics to estimate inflation risk premia in the United States and the euro area. To sharpen our estimation, we include in the information set macro data and survey data on inflation and interest rate expectations at various future horizons, as well as term structure data from both nominal and index-linked bonds. Our results show that, in both currency areas, inflation risk premia are relatively small, positive, and increasing in maturity. The cyclical dynamics of long-term inflation risk premia are mostly associated with changes in output gaps, while their high-frequency fluctuations seem to be aligned with variations in inflation. However, the cyclicality of inflation premia differs between the US and the euro area. Long term inflation premia are countercyclical in the euro area, while they are procyclical in the US.
Keywords: E43; E44; 330; central bank credibility; inflation risk premia; Term structure of interest rates; Inflationsrate; Risikoprämie; Zinsstruktur; Geldpolitik; Konjunktur; Eurozone; EU-Staaten; USA